Reducing Vulnerability and Building Resilience in the Post-Disaster Context: A Case Study of the 2006 Yogyakarta Earthquake Recovery Effort - Erin Joakim (Teknik Lingkungan Universitas Islam Indonesia, 2012)
As the human and economic costs of natural disaster events have dramatically increased over the past three decades, governments, researchers and humanitarian agencies have increasingly focused on reducing disaster impacts and increasing the resilience of individuals, households and communities. Recent disaster recovery efforts have focused on implementing a holistic social-ecological disaster risk reduction approach popularized through post-2004 tsunami recovery programs under the mantra of ‘building back better’. Although this approach has been increasingly adopted by various government and humanitarian organizations to describe their recovery and reconstruction activities, defining what is meant by ‘better’ and measuring ‘better’ as an outcome has been difficult to conceptualize and operationalize. In order to rectify this gap in the literature, the Post-Disaster Sustainable Livelihoods, Resilience and Vulnerability framework (PD-SLRV) was developed for the purposes of analyzing, evaluating and monitoring disaster recovery using the concepts of vulnerability, resilience and sustainable livelihoods.Using the 2006 Yogyakarta, Indonesia earthquake as a case study, this paper will explore how the concepts of vulnerability, resilience and sustainable livelihoods inform the disaster recovery process, the nature of the relationship between these concepts as well as their usefulness in evaluating disaster recovery efforts. Through a detailed analysis of the various vulnerabilities and resiliencies that exist within recovering communities, the complex and dynamic nature of resilience and vulnerability is revealed, indicating a multifaceted relationship dependent on scale, context and place.